Substitution of Artificial Feed With Seaweed Flour (Gracilaria sp.) Against the Growth of Red Tilapia Fish (Oreochromis sp.) - Andriani, Rovina; Muhdar, Fatma (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
In fish farming, feed is the highest operational cost, accounting for more than 60% of the total production cost. Therefore, to reduce production costs in aquaculture, fish feed can be made yourself. The purpose of this study was to determine the nutritional content of feed and to determine the effect of artificial feeding with the addition of seaweed flour (Gracilaria sp.) on the growth of Red Tilapia (Oreochromis sp.). This research was conducted in June-September 2021, the research variables consisted of proximate analysis test, specific growth rate (SGR) and absolute growth. Based on the results of the proximate analysis test on feed, it showed that treatment A with the addition of Gracilaria, sp of 10 g gave the best results by looking at the protein content in the feed on average by 60%, while the effect of feeding with the addition of Gracilaria seaweed, sp on the specific growth rate (SGR) is found in treatment C, which is an average of 0.06%, the best absolute growth average is found in treatment C, which is 33.04 gr.